TINGKAT%2520KETERAMPILAN%2520DASAR%2520SEPAKBOLA%2520SEKOLAH%2520SEPAKBOLA%2520(SSB)%2520PSDM%2520USIA%252010-12%2520TAHUN%2520KECAMATAN%2520PONGGOK%2520KABUPATEN%2520BLITAR%2520TAHUN%25202019 - FAJAR EKO CAHYONO, BOY; SYAFII, IMAM (Jurnal Prestasi Olahraga, 2019)
ABSTRACT THE LEVEL OF BASIC SKILL OF FOTTBALL STUDENTS OF FOOTBALL SCHILL (SSB) PSDM AGE 10-12 YEARS OLD OF PONGGOK, BLITAR IN 2019 Name : Boy Fajar Eko Cahyono Reg : 15060474110 Study Program : Bachelor of Sport Coaching Education Faculty : Sport Science Institution : State University Of Sport Football is a sport that is played by 11 players with teams facing each other using a grassy field using a tool in the form of a ball, in a basic technique soccer game becomes a very basic thing that must be possessed by every player, while the basic technique includes passing , dribble, control, heading, juggling, trowh in and shooting. Coaching on this basic technique must also be done from an early age and of course also must pass the correct and designed training. This study aims to determine the level of basic skills of PSDM football school students (SSB) aged 10-12 years. The method used is quantitative and presented in descriptive form. The subjects in this study were all students of SSB PSB Ponggok Blitar, aged 10-12 years, 22 children. Data analysis techniques used are the percentage and frequency. The results of each of the basic skills tests for SSB PSDM football are: 1. Dribble There is 1 student in the "very good" category with an assessment of> 66, then 21 students are in the "good" category with an assessment of 53-65. 2. Short Pass There are 1 students in the "very good" category with an assessment> 124, then 16 students in the "good" category with grades 104-123, then 5 students enter the "medium" category with an assessment of 85-103. 3. Trowh In There are 3 students in the category of "good" with an assessment of 59-69, then 13 students in the category of "moderate" with a rating of 47-58, then 5 students in the category of "less" with an assessment of 36-46 the last 1 person with the category of "very less" with an assessment <35. 4. Running With the ball There are 15 students in the category of "very good" with an assessment of> 57, then 7 students with the category of "good" with an assessment of 48-56. 5. Heading There are 1 students in the category of "good" with a rating of 67-81, then 12 students in the category of "medium" with a rating of 52-66, then 9 students in the category of "less" with an assessment of 37-51. 6. Shooting At the ball There are 3 students in the category of "medium" with a rating of 44-54, then 10 students in the category of "less" with a rating of 32-43, then 9 students in the category of "very less" with an assessment <31. The results of this study are the level of All shows that in the category of "moderate" with a percentage of 77.27%, the basic skills of dribbling students (SSB) PSDM included in the category of "good" with a percentage of 95.46%, basic skills of short pass students (SSB) PSDM is included in the "good" category with a percentage of 72.73%, the basic skills of students trhow in (SSB) PSDM is included in the "medium" category with a percentage of 59.10%, the basic skills of running with the ball students (SSB) PSDM are included in the category of "very good" with a percentage of 68.18%, the basic skills of students heading (SSB) PSDM included in the category of "moderate" with a percentage of 54.55%, the basic shooting skills of students (SSB) PSDM included in the category of "less" with a percentage of 45 , 46%. So from the above explanation it can be concluded that SSB PSDM students aged 10-12 years as many as 22 students dominated in the "medium" category with 17 students with a percentage of 77.27%. From these results it is hoped that the trainer will focus more on exercises in which students are still not mastered, such as the basic techniques of trowh in, heading and left foot shooting where in the basic technique the average student gets in the category of "medium" and "less". The author also hopes that this research can improve the basic techniques of SSB PSDM students. Keywords : Skills, coaching, achievement, soccer, early age. ABSTRAK TINGKAT KETERAMPILAN DASAR SEPAKBOLA SEKOLAH SEPAKBOLA (SSB) PSDM USIA 10-12 TAHUN KECAMATAN PONGGOK,KABUPATEN BLITAR Name : Boy Fajar Eko Cahyono Reg : 15060474110 Program studi : S-1 Pendidikan Kepelatihan Olahraga Fakultas : Faklutas Ilmu Olahraga Instansi : Universitas Negeri Surabaya Sepakbola adalah salah satu olahraga yang dimainkan dengan jumlah 11 pemain dengan tim yang saling berhadapan menggunakan sebuah lapangan berumput dengan menggunakan alat berupa bola sepak, dalam permainan sepakbola teknik dasar menjadi suatu hal yang sangat mendasar yang harus dimiliki oleh setiap pemain, adapun teknik dasar tersebut meliputi passing, dribble, control, heading, juggling, trowh in dan shooting. Pembinaan pada teknik dasar ini juga harus dilakukan sejak dini dan tentunya juga harus melewati latihan yang benar dan terancang. Penelitian ini memiliki tujuan untuk mengetahui tingkat keterampilan dasar sepakbola siswa sekolah sepakbola (SSB) PSDM usia 10-12 tahun. Metode yang digunakan adalah kuantitatif dan disajikan dalam bentuk deskriptif. Subjek dalam penelitian ini adalah seluruh siswa SSB PSDM Ponggok Blitar usia 10-12 tahun 22 anak. Teknik analisis data yang digunakan adalah presentase dan frekuensi. Adapun hasil masing masing tes keterampilan dasar sepakbola SSB PSDM yaitu: 1. Dribble Terdapat 1 siswa dengan kategori ?baik sekali? dengan penilaian > 66, kemudian 21 siswa masuk kategori ?baik? dengan penilaian 53-65. 2. Short Pass Terdapat 1 siswa dengan kategori ?baik sekali? dengan penilaian > 124, kemudian 16 siswa dengan kategori ?baik? dengan penilaian 104-123, kemudian 5 siswa masuk kategori ?sedang? dengan penilaian 85-103. 3. Trowh In Terdapat 3 siswa dengan kategori ?baik? dengan penilaian 59-69, kemudian 13 siswa dengan kategori ?sedang? dengan penilaian 47-58, kemudian 5 siswa dengan kategori ?kurang? dengan penilaian 36-46 yang terakhir 1 orang dengan kategori ?kurang sekali? dengan penilaian < 35. 4. Running With the ball Terdapat 15 siswa dengan kategori ?baik sekali? dengan penilaian > 57, kemudian 7 siswa dengan kategori ?baik? dengan penilaian 48-56. 5. Heading Terdapat 1 siswa dengan kategori ?baik? dengan penilaian 67-81, kemudian 12 siswa dengan kategori ?sedang? dengan penilaian 52-66, kemudian 9 siswa dengan kategori ?kurang? dengan penilaian 37-51. 6. Shooting At the ball Terdapat 3 siswa dengan kategori ?sedang? dengan penilaian 44-54, kemudian 10 siswa dengan kategori ?kurang? dengan penilaian 32-43, kemudian 9 siswa dengan kategori ?kurang sekali? dengan penilaian < 31. Hasil dari penelitian ini adalah tingkat Seluruh Keterampilan Dasar Sepakbola menunjukan bahwa dalam kategori ?sedang? dengan persentase 77,27%, keterampilan dasar dribbling siswa (SSB) PSDM masuk dalam kategori ?baik? dengan persentase 95,46%, keterampilan dasar short pass siswa (SSB) PSDM masuk dalam kategori ?baik? dengan persentase 72.73%, keterampilan dasar trhow in siswa (SSB) PSDM masuk dalam kategori ?sedang? dengan persentase 59,10%, keterampilan dasar running with the ball siswa (SSB) PSDM masuk dalam kategori ?baik sekali? dengan persentase 68,18%, keterampilan dasar heading siswa (SSB) PSDM masuk dalam kategori ?sedang? dengan persentase 54,55%, keterampilan dasar shooting siswa (SSB) PSDM masuk dalam kategori ?kurang? dengan persentase 45,46%. Jadi dari penjelasan diatas dapat dapat disimpulkan bahwa siswa SSB PSDM usia 10-12 tahun sebanyak 22 siswa masih mendominasi dikategori ?sedang? dengan jumlah 17 siswa dengan persentase 77,27%. Dari hasil tersebut diharap pelatih lebih memfokuskan latihan-latihan yang sekiranya para siswa masih belum menguasai, seperti di teknik dasar trowh in, heading dan shooting dengan kaki kiri yang dimana pada teknik dasar tersebut rata rata siswa mendapat dikategori ?sedang? dan ?kurang?. Penulis juga berharap dengan penelitian ini mampu meningkatkan teknik dasar pada siswa SSB PSDM. Kata kunci : Keterampilan, pembinaan, prestasi, sepakbola, usia dini.